2018
DOI: 10.1111/jan.13565
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi study to identify the core components of nurse to nurse handoff

Abstract: This is the first study to identify the core components of nurse-nurse handoff. Subsequent testing of the core components will involve evaluating the handoff approach in a simulated and then actual patient care environment. Our long-term goal is to improve patient safety outcomes by validating an evidence-based handoff framework and handoff curriculum for pre-licensure nursing programmes that strengthen the quality of their handoff communication as they enter clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…In addition to selecting which items should be included in an evidence-based, shift-to-shift nursing handover standard, this study sought to find a consensus about information flows, best practices, and patient involvement. The significant number of nurse experts involved in our survey determined the need for an electronic data collection method [ 30 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to selecting which items should be included in an evidence-based, shift-to-shift nursing handover standard, this study sought to find a consensus about information flows, best practices, and patient involvement. The significant number of nurse experts involved in our survey determined the need for an electronic data collection method [ 30 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature. A Delphi study to identify core components of nursing handover reached 87% consensus to include patient summary information such as diagnosis, code status, medical history, vital signs, physical assessment, labs and medications (O’Rourke et al, 2018). Another study found 72% of handover content consisted of chief complaint, clinical condition, clinical impression, hospital course, current and ongoing issues, results, and invasive devices (Nasarwanji et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The basic idea for all types is that a group of experts provides a more reliable judgement than an individual (Davidson, 2013; Diamond et al., 2014; Giannarou & Zervas, 2014; Hasson et al., 2000; Helms et al., 2017; Hsu & Sanford, 2007; Keeney et al., 2006). It has been widely adopted in medical and nursing research, as in other research fields (Giannarou & Zervas, 2014; Keeney et al., 2006; O'Rourke et al., 2018). Using the PPCs list as a starting point, the endpoint of this study was to achieve consensus on preventable complications on which nursing can have an impact (Hughes et al., 2006, 2013).…”
Section: Methodsmentioning
confidence: 99%